2013
DOI: 10.1002/sia.5239
|View full text |Cite
|
Sign up to set email alerts
|

The electrocatalytic behavior of electrodeposited Ni–Mo–P alloy films towards ethanol electrooxidation

Abstract: Ternary Ni-Mo-P thin films have been electrodeposited from citrate-based electrolyte onto graphite substrates for application as anode catalysts for ethanol electrooxidation. The operating deposition parameters were optimized to produce Ni-Mo-P alloy films of outstanding catalytic activity. The phase structure of the deposits was evaluated employing X-ray diffraction technique. Morphology and chemical composition of the deposited alloy films were studied using scanning electron microscopy and energy-dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…b reveals the presence of two phases. Apart from single broad peak corresponds to the amorphous state of Ni at about 45 o, , there are five sharp peaks at 36.3 o , 42.2 o , 61.2 o , 73.2 o and 77.1 o characterized for TiCN particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b reveals the presence of two phases. Apart from single broad peak corresponds to the amorphous state of Ni at about 45 o, , there are five sharp peaks at 36.3 o , 42.2 o , 61.2 o , 73.2 o and 77.1 o characterized for TiCN particles.…”
Section: Resultsmentioning
confidence: 99%
“…Ni or its composite as a catalyst was used for electrooxidation of small organic molecules such as methanol and ethanol . Our previous work demonstrated that the incorporation of submicron or nanoparticles deposited with Ni or Cu matrix improves its electrocatalytic activity and stability toward electrooxidation of methanol and glucose in alkaline solutions . So far little work has been reported in the literatures concerning investigating the role of nitride or carbide in enhancing the catalytic activity of Ni catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In alcoholic fuel cells, catalysts are necessary to split oxygen molecules at the cathode and breakdown the complex fuel at the anode. In other words, electrocatalyst activates both alcohol chemisorptions and water molecule to provide preferential sitefor OHadsorption [21] as represented by the following equations in acid medium: It is also well known that, the electrooxidation of organic compounds, as a general, in alkaline media, requires the presence of oxyhydroxide group [14,15,[22][23][24][25].…”
Section: Catalysts and Their Role In Fuel Cellsmentioning
confidence: 99%
“…The corresponding electrocatalytic mechanisms of alcohol electrooxidation in alkaline media on Ni, Cu, or Ag catalyst electrodes have been represented, respectively, as follows: On nickel (Ni) catalyst [14,15] Ni (OH)2 + OH -= NiOOH + H2O + e -NiOOH + alcohol = Ni (OH)2 + oxidation product On copper (Cu) catalyst [23] Cu2O + 2OH -= 2CuO + H2O + 2e -CuO + OH --e -= CuOOH CuOOH + CH3OH + 5/4O2=Cu (OH)2+CO2+3/2H2O On silver (Ag)catalyst [24,25]…”
Section: Catalysts and Their Role In Fuel Cellsmentioning
confidence: 99%
“…The limited choice of efficient, highly active, available, and cheap anode catalysts for DAFCs is still a great challenge for energy conversion systems [6]. Considerable efforts have been devoted to the fabrication of high performance Ni-based catalysts for the electrooxidation of methanol and ethanol in alkaline media [7][8][9][10][11][12][13]. Ni is a relatively low cost material and is produced in large amounts; moreover, it displays potential catalytic properties in a wide number of processes such as energy conversion in alkaline fuel cells [14,15].…”
Section: Introductionmentioning
confidence: 99%